The Effect of Resistance Training on Performance of Gross Motor Skills and Balance in Children with Spastic Cerebral Palsy - Ebrahim Zarrinkalam; Majid Ebadi Fara (Islamic Azad University, Hamedan Branch, 2016)
Objective: Cerebral palsy is the most common chronic motor disability in children and can have negative effect on motor functions. The purpose of this study was to investigate the effect of eight weeks resistance training on gross motor ability, balance and walking speed in a group of such children. Methods: 21 cerebral palsy boys with spastic diplegia, aged between 12 and 16 years (mean, 13.66 years), participated in this study. A pre-test, involving walking, sitting, standing and walking up stairs. They were randomly divided into an experimental and control groups. Then, the experimental group participated in 8 weeks of resistance training.  The data was attained from a 10 meter walk test, Berg Balance Test, gross motor ability Section E, D and GMFCS tests.  Kolmogorov-Smirnov test, sample t-test were used for analyzing the data. Results: The results showed a significant improvement in the performance of experimental group in gross motor abilities section  E and D, balance and walking speed after 8 weeks of resistance training (P <0.05(. However, significant differences were not observed in the control group before and after the study (P <0.05).  Conclusion: The results showed that resistance training improves gross motor ability, balance and gait in children with cerebral palsy hence, it is recommended that resistance exercise be used as a therapeutic modality for children with cerebral palsy.